2012
DOI: 10.4103/0019-5049.98769
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between spinous process dimensions and ease of spinal anaesthesia

Abstract: Background:Neuraxial anaesthesia, despite being a common technique, may pose some technical challenges leading to complications such as post-dural puncture headache, trauma to neural structures and neuraxial haematoma. We hypothesised that the interspinous gap (ISG) and the spinous process width (SPW) could be used as objective measures to predict ease of access to the neuraxial space.Methods:Two hundred and two consecutive patients scheduled to have spinal anaesthesia for various surgical procedures were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 7 publications
1
12
0
2
Order By: Relevance
“…Moreover, a greater body weight contributes to difficult needle placement due to more body fat, less flexibility and less prominent bony landmarks. Therefore, this explains the similar findings in both the present study and that of Shankar H et al 9 Thus, it is observed that BMI is the main determinant for the ease of placement of spinal needle in most studies. It can also be understood that a lesser height and greater weight leading to greater BMI is an impediment to easy lumbar puncture.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, a greater body weight contributes to difficult needle placement due to more body fat, less flexibility and less prominent bony landmarks. Therefore, this explains the similar findings in both the present study and that of Shankar H et al 9 Thus, it is observed that BMI is the main determinant for the ease of placement of spinal needle in most studies. It can also be understood that a lesser height and greater weight leading to greater BMI is an impediment to easy lumbar puncture.…”
Section: Discussionsupporting
confidence: 92%
“…The depth to the neuraxial space and BMI was shown to be a predictor of success, along with the practitioner's experience in a more recent study by Kim JH et al, Shankar H et al, could not calculate BMI in all subjects due to missing height data in 119 subjects. 8,9 Chien et al, reported that age and gender were not associated with the first-level success or first attempt success. 10 Ravi KK et al, found that as the weight of the patients increased, the depth of the epidural space also increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grau et al mentioned that the mean of intervertebral spaces for pregnant females was 10.7 mm, while in non-pregnant females it was 11.6 mm (P value < 0.006) ( 9 ). However, no study mentioned the size of intervertebral spaces among Indonesian population ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other neuraxial techniques, spinal anesthesia has some technical complications, such as postdural puncture headache (PDPH), hematoma, and damage to neural structures (6). …”
Section: Introductionmentioning
confidence: 99%